Gambaran Religiusitas Mahasiswa Penyintas Depresi - Norani, Norani; Faridah, Siti; Fadhila, Mahdia (TAUJIHAT: Jurnal Bimbingan Konseling Islam, 2022)
Depression is the second leading cause of death in the world. Depression among students occurs not only in Indonesia but also in the world. Therefore, it is important to study depression among students. Religiosity and mental health are two things that are interrelated because religion is a human nature. So the solution to be able to overcome mental problems is to practice religious values ​​in everyday life. Because the closer a person is to God and the more worship he has, the more peaceful his soul will be, so he will be able to face disappointments and problems in life. This is what underlies the researcher to conduct research on the religiosity of depression survivors. This study aims to describe the religiosity of depression survivors at UIN Antasari Banjarmasin. This study uses a qualitative case study method, the research subject is one person with a history of having experienced major depression. Collecting data using in-depth interviews, observation, Beck Depression Inventory II scale and religiosity scale. The results of the study show a picture of the subject's religiosity, namely in the dimension of belief, the subject has a strong belief in Allah SWT. In the dimension of worship, the subject performs mandatory worship regularly, but for sunnah worship, the subject still rarely does it. So it can be said that the dimensions of worship are quite good. In the practical dimension, the subject realizes religious values ​​well in his daily life. In the dimension of knowledge, the subject has a religious teaching background from his parents and formal education in Islamic boarding schools and Madrasah Aliyah Negeri, so that the subject has broad insight and good religious knowledge. In the dimension of experience, the subject experienced depression as a form of reprimand for neglecting Allah SWT. Where the picture of the subject's religiosity is influenced by parental teaching, religious experience factors, life factors and intellectual factors.